Pancreatic Tumors - Delgado, Bolívar; Etala, Emilio; Mainetti, José M; Piacenza, Guillermo; Torterolo, Edgardo; Vercelli, Jorge (Cirugía del Uruguay, 1980)
New study procedures have rendered preoperatory diagnosis possib